Analysis of the possibility of solid-phase ignition of coal fuel; Energy; Vol. 288 - Kuznetsov G. V. Geny Vladimirovich; Syrodoy S. V. Semen Vladimirovich; Purin M. V. Mikhail Vladimirovich; Karelin V. A. Vadim Aleksandrovich; Nigay N. A. Nataljya Andreevna; Yankovsky S. A. Stanislav Aleksandrovich; Isaev S. A. Sergey Aleksandrovich (2024, 2024)
Title screen